The good, the bad and the ugly - a Swedish qualitative interview study about the landscape of meaning-imbued, exercise-related physical pain, as experienced by 'normal' gym-users - Pelle Pelters (BMC, 2024)
Abstract Background The gym is a well-known place for health promoting or rehabilitating exercise whose availability to all is regarded significant for people's personal health work and the public's health. In this context, physical pain is usually discussed as something negative that people seek to dispose of. However, certain painful experiences appear to be an appreciated part of the gym experience. To investigate this seemingly contradictory landscape of meaning-imbued physical pain, the study aims to explore the different kinds of physical pain present at the gym and their significance for exercising, as experienced by 'normal' gym-users. Methods 24 semi-structured in-depth interviews with active, dedicated, reasonably healthy (= normal) adult gym-users have been analyzed using qualitative content analysis from a hermeneutical stance. Results Participants differentiate between three kinds of physical pain: the good pain of enhancement (often connected to muscle soreness and effort burn), the bad pain of impediment (primarily related to acute damage) and the composite, neutral pain of acceptance (potentially linked to all pains). Conclusion When pursuing the goal of personal health development, normal gym-users argue that exercising at the gym means to expose yourself to pain and to do so willingly, even longingly. Refusing to share this understanding may diminish people's chances to occupy the gym space and, hence, reduce their chances to promote their health.